Determinasi Harga Saham : Suku Bunga, Current Ratio, ROA, dan DER (Value : Jurnal Manajemen dan Akuntansi, 2025)
Oil and gas sector companies are experiencing share price growth. This happened after an increase in global crude oil prices. In addition to global crude oil prices, there are many other factors that influence the rise and fall of stock prices. This study was conducted to find internal and external factors of the company that contribute to the movement of stock prices. The interest rate variable is used as an external factor of the company, while the internal variables are current ratio, ROA, and DER. The research method used is quantitative, with a total research sample of 60 companies. This study uses data on oil and gas companies listed on the IDX for the period 2021 to 2023. The data was processed through a multiple linear regression test approach, using the SPSS Statistics 26. The results obtained from the research are that two variables, namely current ratio and ROA, partially have a significant effect on stock prices, while interest rates and DER are partially insignificant to stock prices.
Keywords: Interest Rates; CR; ROA; DER; Stock Price